Teknik Audio Forensik untuk Analisis Rekaman Suara sebagai Barang Bukti Digital - hendra hendra; silvana rasio henim (Politeknik Caltex Riau, 2021)
Technology plays an important role in everyday life for many people. Then, the problem that arises is the use of technology that is not appropriate and misuses it for personal interests, giving rise to cyber crimes such as drug transactions. The existence of digital evidence can assist in uncovering cases of cyber crimes using digital evidence of sound recordings. Therefore, this research is expected to reveal these cyber crimes. Efforts to analyze sound recordings are carried out using audio forensic techniques to show ownership of voices so that they can be used as evidence. A minimum of 20 words are required that have similarities between the voice of the evidence and the voice of the subject. From the results of the study, it was found that sample A had identical words with evidence of more than 20 words. Sample A has 21 identical words in pitch analysis, 5 words in ANOVA statistical analysis, 26 words in graphical distribution analysis and 24 words in spectrogram analysis of the 30 words analyzed. It can be concluded that audio forensic techniques can show ownership of sound recordings with the results of voice recordings of sample A being identical to the evidence